Legal and Judicial Ethics: Issues of Professional Responsibility and Integrity - Nomuulin, Ochirbat; Narangerel, Sodovsuren (Advances in Social Sciences Research Journal, 2025)
The aim of pour study is explain to interrelated principles of professional responsibility and integrity in both legal and judicial contexts, this article highlights their vital role in maintaining the credibility of the legal profession and the impartiality of the judiciary. Legal and judicial ethics form the foundation of professional responsibility in modern legal systems, ensuring fairness, accountability, and public trust. Legal ethics emphasize principles such as confidentiality, competence, integrity, impartiality, and accountability, which safeguard the attorney-client relationship and promote the proper administration of justice. Judicial ethics, on the other hand, focus on impartiality, independence, integrity, accountability, and diligence as essential conditions for fair and legitimate decision-making. Finally, we studied to defined the issues and theoretical frameworks strengthen respect for the law, professional courtesy, and the avoidance of conflicts of interest, while also zealous yet ethical advocacy and adjudication.